PREVALÊNCIA AUTÁRQUICA NO DESENVOLVIMENTO DAS ATRIBUIÇÕES DESPORTIVAS (Revista Lusófona de Economia e Gestão das Organizações, 2019)
The right to practice sport scientifically referred to as “sport for all” is a fundamental social right ascribed by the Constitution of the Portuguese Republic to all citizens in an equal and non-discriminatory manner, according to its art. 79th and that produces several salient benefits, both individuals and citizenship. Due to its importance, the State in a broad sense (Government, Autonomous Regions and Local Authorities) is constitutionally assigned the task of promoting, stimulating, guiding and supporting this universal right to sport. However, given that all these territorial entities enjoy their duties, and their bodies are consequently competent, in order to develop physical activity, legal abuses may occur between them. Thus, in order to clarify these attributions and competences, it was scientifically intended to analyze, based on the principles of Local Self-Government and Decentralization, but primarily on the Principle of Subsidiarity and in case of legal doubt, which three public entities should be granted the function of their propagation. This investigation, which for reasons presented, will normally conclude the development of these attributions by Local Authorities when there is overlap. Keywords: Right to Sport for All, Assignments and Skills, Local Authorities, Principle of Subsidiarity